PERILAKU KONSUMTIF MAHASISWA: SEBERAPA BESAR PERAN FINANCIAL LITERACY, LIFE STYLE, E-MONEY, DAN SELF CONTROL? - Devi Kusmiati; Heny Kurnianingsih (ITB AAS INDONESIA Surakarta, 2022)
Consumptive behavior is the attitude of people who like to shop and are more concerned with their wants than their needs. The study was conducted to determine whether consumptive behavior can be influenced by financial literacy, lifestyle, electronic money and self-control. The population based on this study were students of the Surakarta Faculty of Economics and obtained a sample of 330 students. The questionnaire in this study is useful for collecting respondent data. Consumptive behavior is partially influenced by lifestyle variables, electronic money, and self-control, in contrast to financial literacy which is stated to affect student consumptive behavior. After being tested simultaneously, the dependent variable is influenced by the independent variables used. The study stated that the consumptive behavior variable (Y) was influenced by 56.6% by the variables of financial literacy (X1), lifestyle (X2), electronic money (X3), and self-control (X4). Then the side of 43.4% is influenced by other factors that were not found in the study